A Thematic Analysis of The Challenges Faced by SME’s during Uncertain Times in KwaZulu-Natal: A case of DACT Beneficiaries - Khoza, Silindile Zanele Maureen; Adeniyi, Adeshina Olushola; Ayandibu, Ayansola Olatunji (The Journal of Accounting and Management, 2022)
The small businesses in South Africa exist to help with solutions that respond to the overall economic and social development challenges such as the high levels of unemployment, poverty and inequality. The government’s role has always been to make the business environment conducive for all businesses to thrive. Despite the efforts by government, SMEs still experienced several challenges that impede their opportunity to grow and be sustainable in order to fulfil government and society expectations. This study aimed at investigating the challenges faced by SMEs during uncertain times of Covid-19 and Civil unrests within KZN. The study also explored the recommendations to take in order to rebuild again and also to better prepare for future uncertain events. A case study research design was used. The study used a qualitative research approach to gather an in-depth understanding of the challenges faced and actions taken by DACT incubate in KZN. The sample size of 10 SMEs owners was selected from the targeted population of 80 SMEs. The data generated through online zoom interviews was analysed using NVivo 12 software to create themes and sub-themes based on the research questions. The findings indicated that there is a lot of challenges experienced by SMEs that were exacerbated by the outbreak of Covid-19 pandemic and the Civil unrests. These challenges included downsizing employees, losing customers, reducing production due to unavailability of raw materials, losing production time, and drastic drop in sales. Most of SMEs also could not even access purchase order or short-term funding, and available relief support schemes. In conclusion, the study identifies some key recommendations on what DACT incubate, private sector and government can do to respond to SMEs challenges to help them rebuild and contribute to solving economical and societal challenges.